Avaliação do grupo de apoio às vítimas de violência (GAVV) e seu efeito no enfrentamento à violência contra a mulher na cidade de Fortaleza – CE: um estudo entre 2016 a 2023 - Rodrigues, Livia Rocha (2024)
This work dealt with the issue of combating violence against women through public security instruments in Ceará. Gender inequality designates a role of inferiority and submission to women due to male domination in the structure of society. Thus, the social problem of violence is observed through the dissemination of security indicators in the media and social media. Through international conventions adopted by Brazil and the Maria da Penha Law, published in 2006, there are mechanisms that aim to combat domestic violence in the country. One of them is the Support Group for Victims of Violence - GAVV, a service of the Prevention and Community Support Command of the Military Police of Ceará - Copac/PMCE. Through community policing, a philosophy in which there is a partnership of prevention and care between the police and the community, GAVV establishes itself as a group that acts in the face of violence within communities and one of its propositions is to guarantee the safety of abused women , building a relationship with the victim, presenting them with new ways to live without the aggressor and without the situation of violence. Thus, the objective of this study is to evaluate GAVV's performance in protecting and welcoming women victims of violence in the city of Fortaleza between 2016 and 2023. Specifically, it aims to analyze GAVV's institutional trajectory to organize itself as a Program to Combat Violence against Women. Woman in Fortaleza; understand how it is linked to the care and protection network for women who are victims of violence; describe the support that GAVV provides to victims, and understand the dynamics of dialogue between the care provided by GAVV and the perspective of the women served. This study is classified as qualitative and is based on documents such as the Maria da Penha Law and those relating to the Community Police. As for the Evaluative Perspective, it uses the assumptions of the in-depth evaluation of Léa Rodrigues (2008) and Alcides Gussi (2017). It was observed that women and police officers see GAVV's work positively and consider it a way of implementing the feeling of security, welcome and protection. In conclusion, the evaluation of GAVV Fortaleza's activities reveals the importance of this resource in offering support and protection to women in vulnerable situations and the significant impact on combating domestic violence as a whole. Analyzing the functioning of the group, it is clear that they play a crucial role in promoting awareness, preventing new cases and training victims to break the cycle of abuse. However, given the challenges and continuous demand for assistance, it is understood that much still needs to be done to strengthen and expand these resources, both in terms of human resources and dissemination. Therefore, the continuous evaluation and improvement of GAVV'sactivities is crucial to ensure that they can effectively meet the needs of victims and contribute significantly to the construction of a safe and violence-free society.